Gambaran Kejadian Low Back Pain pada Pengendara Motor Ojek Online di Surabaya - Tintin Sukartini; Lailatun Ni'mah; Risma Wahyuningtyas (Critical Medical and Surgical Nursing Journal (CMSNJ), 2019)
Introduction: Low back pain was discomfort sensation in the lower back area or above the gluteal. Low back pain was a potential health problem for ride-hailing riders. This study aimed to describe of low back pain in online ride-hailing in Surabaya.Method: This study was done in Surabaya, used a cross-sectional design. The sample was 100 respondents using a consecutive sampling technique. Data were obtained using a questionnaire and describe using crosstabs statistical.Results: Online ride-hailing experienced low back pain amounts 61% and has not experienced amounts of 39%. Respondents have experienced low back pain aged >30 years (43%), normal BMI (41%), work position (35%), work duration > 8 hours per day (50%), work period > 5 months (52%), smoking (50%), and not exercising (46%).Conclusion: Low back pain incident has a high value that amounts to 61%. Online ride-hailing are advised to pay attention to the duration of work and work position. Enough rest time and apply an ergonomic working position can prevent the fatigue that causes low back pain.